5(x+3)=7(x-4)

Simple and best practice solution for 5(x+3)=7(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+3)=7(x-4) equation:


Simplifying
5(x + 3) = 7(x + -4)

Reorder the terms:
5(3 + x) = 7(x + -4)
(3 * 5 + x * 5) = 7(x + -4)
(15 + 5x) = 7(x + -4)

Reorder the terms:
15 + 5x = 7(-4 + x)
15 + 5x = (-4 * 7 + x * 7)
15 + 5x = (-28 + 7x)

Solving
15 + 5x = -28 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
15 + 5x + -7x = -28 + 7x + -7x

Combine like terms: 5x + -7x = -2x
15 + -2x = -28 + 7x + -7x

Combine like terms: 7x + -7x = 0
15 + -2x = -28 + 0
15 + -2x = -28

Add '-15' to each side of the equation.
15 + -15 + -2x = -28 + -15

Combine like terms: 15 + -15 = 0
0 + -2x = -28 + -15
-2x = -28 + -15

Combine like terms: -28 + -15 = -43
-2x = -43

Divide each side by '-2'.
x = 21.5

Simplifying
x = 21.5

See similar equations:

| 23.45j=-469 | | x+1+x+2+x=180 | | -1(x+12)+8(x+1)=10 | | 6x^2+2x-888=0 | | 5+30x=20x+29 | | 3(10)+5y=10 | | y=ln(5x) | | -1+3x=-3+13x | | 2x+10=4x+34 | | -2x+3=2x-1 | | 12.3+4x=2x-9.2 | | 10x-15=9x+10 | | 59-3x=5-9x | | x+10=-47 | | x+2+1=9 | | 7x-5=5x+27 | | 6c-86=3c-14 | | 3x+18=6x-9 | | 6x+6=-38-5x | | 3ab+7b= | | 7+6x=-18+x | | 6x^2+6y^2=144 | | 7+6x=-18x+x | | 13-3x=5-2x | | -4x+14=54 | | 9h+10h+7h-6h-16h=10 | | 6(x+2)=6x+14 | | 4(x+6)+3=-3 | | 11r^2-15r=-4 | | 5+65c=39c+13 | | 17j-16j-j+j=16 | | 6k-4k-k=12 |

Equations solver categories